AN EMPIRICAL STUDY OF EMOTIONAL LABOR ON CUSTOMER LOYALTY INTENTIONS WITH MEDIATING ROLE OF PERCEIVED SERVICE QUALITY IN BANKING SECTOR - Kashif, Muhammad (2022)
The study aimed to investigate the relationship between emotional labor strategies and customer loyalty intentions with mediating role of perceived service quality between them. A theoretical model was developed to test the association among emotional labor strategies (surface acting and deep acting), customer loyalty intentions and perceived service quality. A causal research design was employed, while quantitative data provided support for the hypotheses from participants of 350 bank customers recruited by convivence sampling in Malakand division KP, Pakistan. The results demonstrated that emotional labor strategies i.e., deep acting and surface acting differentially affect customers' loyalty intentions. Likewise, the effect of deep acting on customer loyalty intentions is comparatively more than the effect of surface acting. Furthermore, perceived service quality significantly mediates the relationship between emotional labor and customer loyalty. The findings of this study suggest that employers need to regulate deep acting instead of surface acting among employees to gain long term customer loyalty. Therefore, the efforts to build long term customer relationship by customer loyalty might effectively be accomplished. Despite contribution this study has few limitations. first the collected data of this study is not from all provinces of pakistan, because of large geographical dispersion and less financial resources. Second the less understanding of respondents about study variables such as emotional labor and service quality. Third, the study is limited to customers and employs quantitative research method. To understand the topic more holistically and thoroughly explanatory mixed-method research approach and data from both customer and employees will be required. Future studies may consider these limitations as a gap for further research.